2015
DOI: 10.3390/m860
|View full text |Cite
|
Sign up to set email alerts
|

2-Methylsulfanylbenzo[f]isoquinoline

Abstract: S-Methylation of a 4-(naphth-2-yl)-β-thiolactam gives an intermediate 4-(naphth-2-yl) substituted 1-azetine which undergoes a [2+2] ring-opening followed by electrocyclic ring closure of the resulting 2-azadiene to give a benzo[f]isoquinoline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 17 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…We have shown, disappointingly, that the thiazete 1,1-dioxide (5a) is not reactive towards 1,3-dipoles or cyclopropenones, in marked contrast to the 1-azetine system, but that it does undergo rearrangement into the previously unreported 1,2,3-oxathiazolin-2-oxide (21). However, we have produced sixteen new isothiazoloisoxazoles and four new isothiazole 1,1-dioxides building upon the route used to access the thiazete 1,1-dioxide (5a).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have shown, disappointingly, that the thiazete 1,1-dioxide (5a) is not reactive towards 1,3-dipoles or cyclopropenones, in marked contrast to the 1-azetine system, but that it does undergo rearrangement into the previously unreported 1,2,3-oxathiazolin-2-oxide (21). However, we have produced sixteen new isothiazoloisoxazoles and four new isothiazole 1,1-dioxides building upon the route used to access the thiazete 1,1-dioxide (5a).…”
Section: Discussionmentioning
confidence: 99%
“…No reactions of the imine present in the thiazete 1,1-dioxide (5a) were observed, and the starting material was returned unchanged in all cases, a huge disappointment given that we had shown that the imine within the 1-azetine system reacts easily with both nitrile oxides and cyclopropenones. [21][22][23][24] Other 1,3-dipoles (nitrile ylides, nitrilimines, nitrones, aryl azides and azomethine ylides) and dienes were found to be similarly unreactive. Interestingly, when the cyclopropenone reaction was attempted in the presence of a Lewis acid, a reaction was observed.…”
Section: Synthesis and Reactivity Of Isothiazole 11-dioxides And Thimentioning
confidence: 99%
See 3 more Smart Citations